Evaluation of Fluorescent Analogs of Deoxycytidine for Monitoring DNA Transitions from Duplex to Functional Structures - Yogini P. Bhavsar; Samantha M. Reilly; Randy M. Wadkins (Journal of Nucleic Acids)
Topological variants of single-strand DNA (ssDNA) structures, referred to as “functional DNA,” have been detected in regulatory regions of many genes and are thought to affect gene expression. Two fluorescent analogs of deoxycytidine, Pyrrolo-dC (PdC) and 1,3-diaza-2-oxophenoxazine (tC∘), can be incorporated into DNA. Here, we describe spectroscopic studies of both analogs to determine fluorescent properties that report on structural transitions from double-strand DNA (dsDNA) to ssDNA, a common pathway in the transition to functional DNA structures. We obtained fluorescence-detected circular dichroism (FDCD) spectra, steady-state fluorescence spectra, and fluorescence lifetimes of the fluorophores in DNA. Our results show that PdC is advantageous in fluorescence lifetime studies because of a distinct ~2 ns change between paired and unpaired bases. However, tC∘ is a better probe for FDCD experiments that report on the helical structure of DNA surrounding the fluorophore. Both fluorophores provide complementary data to measure DNA structural transitions.